Radiologic diagnosis of pulmonary metastases of uterine choriocarcinoma - A. V. Sudarkina; A. P. Dergilev; Yu. V. Chikinev; E. A. Drobyazgin; V. I. Kochura; N. A. Gorbunov (Вестник рентгенологии и радиологии, 2019)
The article describes a rare case of metastatic pulmonary choriocarcinoma manifested with hemoptysis. Obstacles and pitfalls of the diagnosis of uterine choriocarcinoma with atypical manifestation were discussed. The patterns of pulmonary metastases of uterine choriocarcinoma and contribution of cross-sectional imaging modalities to diagnostic work-up were described. For the first time diffusion weighted magnetic resonance imaging of the chest was used for the follow-up examination and diagnosis of the recurrence of the disease.This case is of interest due to unusual clinical and radiological presentation of uterine choriocarcinoma. The article is aimed to radiologists to be familiar with this disease to provide its early diagnosis and timely treatment.